2014
DOI: 10.1016/j.ijid.2014.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carriage of Streptococcus pneumoniae in Romanian children before the introduction of the pneumococcal conjugated vaccination into the national immunization programme: a national, multi-centre, cross-sectional observational study

Abstract: In Romanian children, the majority of carried S. pneumoniae isolates are vaccine serotypes. The isolates with MICs defining macrolide resistance were very frequent, as well as the isolates with MICs defining penicillin resistance in the case of meningitis or penicillin dose-dependent susceptibility for other infections, mainly for the strains belonging to PCV13 serotypes. The implementation of PCV13 within the Romanian national immunization programme could reduce the circulation of these strains with higher ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…This specific broth enrichment combining STHB, yeast, and rabbit serum has been shown to improve pneumococcal isolation compared to conventional culture-based results by 16% [38]. Although the detected colonization prevalence was higher in our study, the proportion of PCV10-serotypes (37.3%) among children aged <5 years was similar to the results reported in other studies from Kenya, the Gambia and Nigeria [31, 46, 61, 62]. …”
Section: Discussionsupporting
confidence: 86%
“…This specific broth enrichment combining STHB, yeast, and rabbit serum has been shown to improve pneumococcal isolation compared to conventional culture-based results by 16% [38]. Although the detected colonization prevalence was higher in our study, the proportion of PCV10-serotypes (37.3%) among children aged <5 years was similar to the results reported in other studies from Kenya, the Gambia and Nigeria [31, 46, 61, 62]. …”
Section: Discussionsupporting
confidence: 86%
“…In contrast, from the 30 studies assessing carriage unrelated to IPD among children, only 5 studies reported PCV serotypes accounting for more than 50% of the total serotypes. 31,33,40,41,44 It would appear from the current snapshot that the introduction of PCV has had a greater impact in reducing nasopharyngeal carriage of PCV-specific serotypes among children without IPD than on IPD itself; further pneumococcal surveillance in coming years may show an additional impact on IPD cases caused by PCV serotypes in pediatric populations. PCV serotypes were responsible for >60% of total serotypes in IPD cases in few studies among adults aged 65 y and older 6,58 and 15-59 y.…”
Section: Discussionmentioning
confidence: 98%
“…25 In contrast, conjugate vaccine serotypes causing non-IPD conditions among children were more than 50% prevalent in only 5 of 30 studies (Table 1). 31,33,40,41,44 Prevalence of serotypes uniquely covered by PPV23 was reported in a total of 33 papers. Most often ranking in the top 3 among those serotypes in PPV23 but not in PCV13 for IPDrelated pneumococcal illness were serotypes 15B (or 15B/C) reported in 9 papers 6,[8][9][10]15,17,20,24,26 at up to 11.8% prevalent, 26 5 papers reporting serotype 22F ( 11.3%) 15 Prevalence of serotypes not covered by any pneumococcal vaccines (i.e., PCV13 or PPV23) was reported in a total of 34 papers.…”
Section: Pneumococcal Serotype Distribution Among Children Aged Undermentioning
confidence: 99%
“…IR13 was of ST81 and thus belongs to the clone Spain 23F -1; IR52 was of ST558, to which serotype 35B isolates from different continents also belong; and all others displayed new STs ( Table 1 ). The serogroup was determined for 11 Romanian isolates: 10 were serogroup 19, which is prevalent in Romania ( 30 , 31 ), and 1 was serogroup 6.…”
Section: Resultsmentioning
confidence: 99%